2019
DOI: 10.1021/acs.biomac.9b01556
|View full text |Cite
|
Sign up to set email alerts
|

Neat Ionic liquid and α-Chymotrypsin-Polymer Surfactant Conjugate-Based Biocatalytic Solvent

Abstract: Performing biocatalysis in nonaqueous solvents is advantageous as it imparts enhanced solubility to hydrophobic substrates and an ability to increase the temperature for shifting reaction equilibrium in the forward direction. In this work, we show the design and development of another class of nonaqueous composite solvent obtained by mixing surface modified enzyme and neat ionic liquid (IL). We systematically probe the interaction and solubility of industrially relevant α-chymotrypsin in its native or surface-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Overall, this work provides valuable insights for the dissolution of both specific and non‐specific binding dyes in the non‐aqueous protein polymer conjugated liquid/solvent matrix. Moreover, our recent studies have shown an another class of neat ionic liquid and enzyme‐polymer surfactant bio‐conjugate based bio‐catalytic solvent medium . It can be envisaged that in conjunction with ionic liquids, the current study of dissolving and dispersing various dyes in bioconjugates can pave a path forward for design and development of solid state electrolytes and lasing dye media for potential applications.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Overall, this work provides valuable insights for the dissolution of both specific and non‐specific binding dyes in the non‐aqueous protein polymer conjugated liquid/solvent matrix. Moreover, our recent studies have shown an another class of neat ionic liquid and enzyme‐polymer surfactant bio‐conjugate based bio‐catalytic solvent medium . It can be envisaged that in conjunction with ionic liquids, the current study of dissolving and dispersing various dyes in bioconjugates can pave a path forward for design and development of solid state electrolytes and lasing dye media for potential applications.…”
Section: Discussionmentioning
confidence: 97%
“…Methods : Stock solutions of Rh6G and FL were prepared by dilution of concentrated Rh6G and FL dissolved in water and concentration of Rh6G and FL were determined from respective molar extinction coefficient of ϵ 526 nm =81,000 M − 1 cm −1[69] and ϵ 490 nm =76,000 M −1 cm −1 . Stock solution of native BSA was prepared in 10 mM pH 7.4 phosphate buffer and concentrations of nBSA and PSpBSA sol were determined from molar extinction coefficient of ϵ 280 nm =43,824 M −1 cm −1 . UV‐Vis measurements were done using Cary Varian 100 spectrophotometer, steady‐state emission spectra were recorded using Varian Eclipse Fluorescence spectrophotometer and bright field optical micrographs were taken using Olympus BH2 microscope and temperature‐dependent microscopic studies were performed using Linkam stage (TP 94 and LNP).…”
Section: Methodsmentioning
confidence: 99%
“…The modification enhanced the solubility of the enzyme in neat protic and neat aprotic ionic liquids (N-methyl-2-pyrrolidonium trifluoromethanesulfonate; [NMP][OTf]), or (1-methyl-3-(4-sulfobutyl)-1H- imidazol-3-ium trifluoromethanesulfonate; [HO 3 S(CH 2 ) 4 MIM][OTf]) respectively and retained a similar β-sheet structure to the native protein in aqueous solution. The unmodified enzyme was insoluble in the ILs [ 95 ].…”
Section: Ionic Liquids and Isolated Enzymesmentioning
confidence: 99%
“…Mukhopadhayay et al also demonstrated that ionic liquids could be used to improve the activity of solvent-free liquid α-chymotrypsin, further evidence to the effectiveness of the strategy. 78…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%